The Role of Social Norms and Social Awareness in Forming the Intention to Pay Zakat: at LAZ Harfa Serang City - Raden Arisna; M. Sulaeman Jajuli; Budi Sudrajat; Zaini Ibrahim; Suryani (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of social norms on social awareness and intention to pay zakat, as well as the influence of social awareness on the intention to pay zakat. The study used a quantitative approach with a survey method of 124 Muslim respondents who met the criteria as muzakki at LAZ Harfa Serang City. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results showed that social norms had a positive and significant effect on social awareness with a t-statistical value of 21.954 and p-values of 0.000, and were able to explain 74% of the variance of social awareness (R² = 0.740). In addition, social norms also have a positive and significant effect on the intention to pay zakat with a t-statistical value of 2.793 and p-values of 0.005. Social awareness has been proven to have a positive and significant effect on the intention to pay zakat with a t-statistical value of 3.608 and p-values of 0.000. Simultaneously, social norms and social awareness were able to explain 85.3% of the variance in the intention to pay zakat (R² = 0.853), with an SRMR value of 0.075 which indicates a good model suitability. These findings confirm that social awareness plays an important role as a mechanism that bridges the influence of social norms on the intention to pay zakat. Therefore, strengthening social norms and increasing public social awareness is a key strategy in encouraging sustainable zakat compliance